PEMANFAATAN LIMBAH PELEPAH DAN DAUN KELAPA SAWIT MELALUI FERMENTASI Trichoderma sp. SEBAGAI PAKAN SAPI POTONG - Akhmad Rizali; Fachrianto Fachrianto; M. Hafiz Ansari; Anis Wahdi (EnviroScienteae, 2018)
The dependence on imports of feed ingredients for ration composer are increasingly expensive and availability of limited and unsustainable local feed, causing the low level of production and reproduction of local Indonesian cattle. This study aims to exploit the potential of plantation waste as an alternative feed of beef cattle, increase the nutrient value and digestibility of waste of palms and leaves and to know the optimal use of inoculums (Trichoderma sp.) through fermentation in improving the digestibility and nutritional value of the feed. The research method used was a complete randomized design (RAL) with five treatments and three replications, with 14 days fermentation. The research treatment includes: PD 0 (without Trichoderma/control), PD 1 (fermentation using Trichoderma viride 3 ml), PD 2 (fermentation using Trichoderma viride 6 ml), PD 3 (fermentation using Trichoderma harzianum 3 ml), PD 4 (fermentation using Trichoderma harzianum 6 ml).O Observation parameters observed included dry matter (DM), crude protein (CP), ash content (AC), coarse fat (CF), organic matter (OM), and total digestible nutrient (TDN). The data obtained were analyzed using variance analysis. The results showed that the best treatment was found in PD 1, had a significant effect on control in increasing total digestible nutrient (TDN) 51.62% and crude fiber decline by 39.14%, although an increase in CP (5.34%) was not equal to the treatment of the PD 4 (5.35%). While the best increase of CP content was found in the treatment of PD 4 of 3.35%. While the best CP content found in the treatment of PD 4 of 5.35%. It was concluded that the use of Trichoderma viride and Trichoderma harzianum can improve the quality of waste nutrient and palm oil leaves by fermentation and the optimal inoculums dose used to produce the best fermentation is the use of Trichoderma sp. 3 ml in 3kg of material.